SCHOOL TV BROADCASTS AS AUD LEARNING MEDIA AT DHARMA WANITA KINDERGARTEN MAOSPATI MAGETAN - Sary Rina Naruvita; Rima Dewi Kartini; Noor Padilah; Sri Watini (Jurnal Scientia, 2022)
Learning resources can be obtained from anywhere, one of which is using digital media, the development of learning resource facilities at this time must be aligned with modern technological developments. The presence of School TV is a form of concern for observers of the world of education and is part of the nation's children's innovation assets that need to be rewarded, because they are able to contribute to the country in the world of education. School TV can be accessed easily anywhere, anyone and anytime as long as we have an internet network. Therefore, the existence of school TV is very useful as an electronic learning resource in developing the learning process. With school TV, children can take advantage of digital media in a positive way. Especially in TK Dharma Wanita Maospati, Magetan, East Java. This activity uses a qualitative description method, collecting data using interviews and documentation. With School TV, educators can increase their creativity in programming, composing learning and educators can make it happen in the form of broadcasts of learning activities at school. This can be used as a digital learning media, to facilitate students in accessing digital learning media.